The Fear of the Lord is Wisdom : a theological introduction to wisdom in Israel - Longman, Tremper, III (Grand Rapids, MI : Baker Academic, 2017)
"Wisdom plays an important role in the Old Testament, particularly in Proverbs, Job, and Ecclesiastes. This major work from renowned scholar Tremper Longman III examines wisdom in the Old Testament and explores its theological influence on the intertestamental books, the Dead Sea Scrolls, and especially the New Testament. Longman notes that wisdom is a practical category (the skill of living), an ethical category (a wise person is a virtuous person), and most foundationally a theological category (the fear of the Lord is the beginning of wisdom). The author discusses Israelite wisdom in the context of the broader ancient Near East, treats the connection between wisdom in the New Testament and in the Old Testament, and deals with a number of contested issues, such as the relationship of wisdom to prophecy, history, and law." -
Pt. 1: The heart of wisdom: Proverbs, Ecclesiastes, and Job -- Proverbs: the fear of the Lord is the beginning of wisdom -- Ecclesiastes: fear God, obey the commandments, and live in light of the coming judgment -- The book of Job: "Behold, the fear of the Lord is wisdom" (Job 28:28) -- Pt. 2: Wisdom elsewhere in the Old Testament -- Other sources of wisdom: Deuteronomy, Psalms, Song of Songs, and prophecy -- Joseph and Daniel: paragons of wisdom -- Adam and Solomon: from the heights of wisdom to the depths of folly -- Pt. 3: Israel's wisdom: cosmopolitan or unique? -- Sources of wisdom: experience, observation, tradition, correction, and ultimately revelation -- Wisdom, creation, and (dis)order -- Israelite wisdom in its ancient Near Eastern setting -- Wisdom, covenant, and law -- Pt. 4: Further refining our understanding of wisdom -- The consequences of wise and foolish behavior: the issue of retribution theology -- The social setting of wisdom -- Wisdom and gender -- Pt. 5: The afterlife of Israel's wisdom -- Intertestamental wisdom from the Apocrypha to the Dead Sea Scrolls -- New Testament wisdom.
Includes bibliographical references and indexes.
Keywords: Wisdom literature -- Criticism, interpretation, etc; Criticism, interpretation, etc